THE ROLE OF APIS IN THE TELECOM TRANSFORMATION TO CLOUD-NATIVE ARCHITECTURE - Kranthi Kumar Pasunuri (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The telecommunications industry is experiencing a transformative shift towards cloud-native architecture, fundamentally reshaping network infrastructure and operations through API integration. This transformation addresses the increasing demands for network agility, operational efficiency, and seamless service delivery in an evolving digital landscape. APIs serve as fundamental building blocks, enabling modular architecture, hybrid cloud orchestration, and automated network management. The implementation of API-driven solutions has revolutionized service deployment, customer experience, and operational efficiency across the telecom sector. Through standardized interfaces and robust integration patterns, APIs facilitate enhanced network slicing, edge computing capabilities, and IoT device management while enabling AI/ML integration for network optimization. This architectural evolution positions telecom providers to meet future connectivity demands while maintaining high reliability, security, and performance standards.